Distribution of trace metal concentrations in paired cancerous and non-cancerous human stomach tissues - Yaman, Mehmet; Kaya, Gokce; Yekeler, Hayrettin (W J G Press, 2007)
AIM: To assess whether trace metal concentrations (which influence metabolism as both essential and non-essential elements) are increased or decreased in cancerous tissues and to understand the precise role of these metals in carcinogenesis. METHODS: Concentrations of trace metals including Cd, Ni, Cu, Zn, Fe, Mg and Ca in both cancerous and non-cancerous stomach tissue samples were determined by atomic absorption spectrometry (AAS). Tissue samples were digested using microwave energy. Slotted tube atom trap was used to improve the sensitivity of copper and cadmium in flame AAS determinations. RESULTS: From the obtained data in this study, the concentrations of nickel, copper and iron in the cancerous human stomach were found to be significantly higher than those in the non-cancerous tissues, by using t-test for the paired samples. Furthermore, the average calcium concentrations in the cancerous stomach tissue samples were found to be significantly lower than those in the non-cancerous stomach tissue samples by using t-test. Exceedingly high Zn concentrations (207-826 mg/kg) were found in two paired stomach tissue samples from both cancerous and non-cancerous parts. CONCLUSION: In contrast to the literature data for Cu and Fe, the concentrations of copper,. iron and nickel in cancerous tissue samples are higher than those in the non-cancerous samples. Furthermore, the Ca levels are lower in cancerous tissue samples than in non-cancerous tissue samples. (c) 2007 The WJG Press. All rights reserved.
Keywords: cancer; trace metals; human stomach; microwave energy; atomic absorption